On Almost Complete Caps in PG(N, q) - Davydov Alexander A.; Marcugini Stefano; Pambianco Fernanda (Cybernetics and Information Technologies, 2018)
We propose the concepts of almost complete subset of an elliptic quadric in the projective space PG(3, q) and of almost complete cap in the space PG(N, q), N ≥ 3, as generalizations of the concepts of almost complete subset of a conic and of almost complete arc in PG(2, q). Upper bounds of the smallest size of the introduced geometrical objects are obtained by probabilistic and algorithmic methods.